PENERAPAN BIM DALAM PERCEPATAN PEMBANGUNAN ASRAMA MAHASISWA NUSANTARA MANADO - Fardi Kalumata; Merci Hosang, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The construction project for the Asrama Mahasiswa Nusantara (AMN) Manado began on December 27, 2023, with a completion time of 247 days. The project is located in Desa Kalasey Dua, Kecamatan Mandolang, Kabupaten Minahasa, Provinsi Sulawesi Utara. The project's owner, PT. Widya Satria, has been tasked with implementing Building Information Modelling (BIM) in the construction process, using BIM 3D, BIM 4D, and BIM 5D. The research methodology used is a literature study and BIM modeling to provide critical work performance data using fast track methods. The results of the analysis are then analyzed using BIM to determine the volume of work, material, and time. BIM implementation using Autodesk Revit and MS-Project helps in reducing the need for resources, such as labor and materials. BIM also facilitates clash detection, allowing the modeling and work schedule to be coordinated and work together. Visual simulations of the project's work progress show that progress is increasing at different stages, with the first stage reaching 3%, the fourth stage reaching 17%, the eighth stage reaching 28%, and the final stage reaching 100%. The project's implementation resulted in a 12.5% increase duration work from the previous 247 days to the new 217 days